Konstruksi Pemikiran Yusuf Al Qaradhawi Tentang Konsep Keadilan Pewarisan Lintas Agama - Mohammad Hendy Musthofa (Institut Agama Islam Sunan Giri Ponorogo, 2026)
ndonesia, as a multicultural nation, faces significant complexity in the application of Islamic law, particularly regarding interfaith inheritance. In classical Islamic jurisprudence, religious difference constitutes an absolute barrier to inheritance between Muslims and non-Muslims; however, the application of this rule in a pluralistic society frequently generates tension between religious norms and the values of social justice. This study aims to examine the construction of Yusuf Al Qaradhawi's thought on the concept of justice in interfaith inheritance as a contextual and socially responsive legal solution within the Indonesian context. A qualitative descriptive approach was employed using the biographical-intellectual (studi tokoh) method, with data gathered through analysis of Al Qaradhawi's primary works and relevant academic journals. The findings reveal that Al Qaradhawi offers a contextual re-reading of the prophetic tradition (hadith) prohibiting interfaith inheritance by distinguishing between kafir harbi (non-Muslims at war with Islam) and kafir dzimmi (non-Muslims living peacefully under Islamic governance), thereby permitting Muslims to inherit from non-Muslims, while the reverse may be facilitated through alternative mechanisms such as hibah (gift), wasiat wajibah (obligatory bequest), and social provisions. This framework is grounded in the principles of maslahah (public interest) and substantive justice through the fiqh al-waqi' approach, which integrates textual sources with contextual realities. It is concluded that Al Qaradhawi's thought makes a significant contribution to the reform of Islamic inheritance law in Indonesia in a manner that is just, inclusive, and responsive to the realities of a multireligious society.